Diet Ibu Hamil Terhadap Kejadian Anemia - Ahyani, Septi; Sunarsih, Sunarsih; Yantina, Yuli (Universitas Malahayati Bandar Lampung, 2022)
Background There are several factors that cause anemia in pregnant women, namely: nutritional status, pregnancy distance, education, parity, maternal age, knowledge, attitudes, and frequency of Antenatal Care (ANC) (Darmawan, 2013). The Ministry of Health (2015) states that the impact that causes anemia in pregnant women is bleeding during childbirth, low birth weight babies (LBW), IQ is not optimal, babies are easily infected and easily suffer from malnutrition, this is due to a lack of knowledge and attitudes of mothers in maintain good Hb levels, such as consuming foods or drinks with low iron content. The purpose of this study was to determine the relationship between dietary factors of pregnant women and the incidence of anemia at the UPT Puskesmas Muncak Kabau Ogan Komering Ulu Timur, South Sumatra in 2021.Methods This type of research is quantitative, descriptive correlation design with cross sectional approach. The population in this study were all pregnant women who experienced anemia at the UPT Puskesmas Muncak Kabau Ogan Komering Ulu Timur, South Sumatra from April to June 2021, totaling 44 respondents and the sample in this study amounted to 44 respondents. In this study the sampling technique used is Total Sampling.Result Based on the results of statistical tests, obtained p-value < value (0.05) which means that there is a relationship between the dietary factors of pregnant women and the incidence of anemia at the UPT Puskesmas Muncak Kabau Ogan Komering Ulu Timur, South Sumatra in 2021, namely (meat consumption: 0.012, eggs: 0.036 and tea: 0.025).In conclusion, there is a relationship between the diet of pregnant women and the incidence of anemiaSuggestion It is hoped that this research can be used as additional information for Puskesmas, especially on MCH in determining health program policies, such as providing socialization about anemia prevention, providing practical classes about good foods for pregnant women to consume and providing counseling to pregnant women who experience anemia. . Keywords: Dietary Factors of Pregnant Women, Anemia Incidence ABSTRAK Latar Belakang Ada beberapa faktor yang menyebabkan terjadinya anemia pada ibu hamil yaitu: status gizi, jarak kehamilan, pendidikan, jumlah paritas, umur ibu, pengetahuan, sikap, dan frekuensi Antenatal Care (ANC) (Darmawan, 2013). Depkes (2015) menyatakan bahwa dampak yang menyebabkan timbulnya anemia pada ibu hamil ialah mengalami pendarahan saat melahirkan, bayi berat lahir rendah (BBLR), IQ tidak optimal, bayi mudah terinfeksi dan mudah menderita gizi buruk, hal ini dikarenakan kurangnya pengetahuan dan sikap ibu dalam menjaga kadar Hb dengan baik, seperti mengkonumsi makanan atau minuman dengan kandungan zat besi yang rendah. Tujuan dalam penelitian ini adalah diketahui Hubungan Faktor Diet Ibu Hamil Terhadap Kejadian Anemia Di UPT Puskesmas Muncak Kabau Ogan Komering Ulu Timur Sumatera Selatan Tahun 2021.Metode Jenis penelitian kuantitatif, Rancangan diskriptif korelasi dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah seluruh ibu hamil yang mengalami anemia Di UPT Puskesmas Muncak Kabau Ogan Komering Ulu Timur Sumatera Selatan terhitung sejak April – Juni 2021 yang berjumlah 44 responden dan Sampel dalam penelitian ini berjumlah 44 responden. Dalam penelitian ini teknik sampling yang digunakan adalah Total Sampling.Hasil Berdasarkan hasil uji statistik, didapatkan p-value < nilai α (0,05) yang artinya terdapat Hubungan Faktor Diet Ibu Hamil Terhadap Kejadian Anemia Di UPT Puskesmas Muncak Kabau Ogan Komering Ulu Timur Sumatera Selatan Tahun 2021 yaitu (konsumsi daging: 0,012, telur: 0,036 dan teh: 0,l025).Kesimpulan ada hubungan diet ibu hamil dengan kejadian anemiaSaran Penelitian ini diharapkan agar dapat dijadikan tambahan informasi bagi Puskesmas khususnya pada KIA dalam menentukan kebijakan-kebijakan program kesehatan, seperti memberikan sosialisasi tentang pencegahan anemia, memberikan kelas praktek tentang makanan-makanan yang baik untuk dikonsumsi ibu hamil serta mengadakan konseling kepada ibu hamil yang mengalami anemia. Kata Kunci : Diet,Ibu Hamil,Anemia